Planned Obsolescence: Myth or Reality? - Yu. B. Nadtochiy, T. G. Apal’kova (International Journal of Advanced Science and Technology, 2020)
This article deals with the issue of objectivity of the existence of an economic phenomenon such as ‘planned obsolescence of products’. The results of the student survey conducted to find out their opinions on the existence of the concept of planned obsolescence, and the data on the repairability of modern electronics are provided below.